Evolução da textura cristalográfica de aços perlíticos submetidos a deformações e tratamentos térmicos distintos - Lima, Pedro Henrique Pinheiro (2022)
Due to human energy needs, non-renewable energy sources are being increasingly explored. For oil, for example, easily accessible reserves are depleted, requiring exploration in deeper or more remote areas, whether land or sea. Marine flexible pipelines are known as the ocean-oil lifeline due to their high flexibility, applicability and recycling, and their responsibility for connecting offshore platforms to subsea production systems. These pipes are subjected to different stress modes, requiring tensile layers responsible for the resistance of these pipes. These layers of elastic shielding in flexible pipelines are constructed by the parallel helical casing of several rectangular wires. Pairs of layers, wound in opposite directions and with different helical shapes are used to provide the required axial force, water depth capability and torsional balance. Due to the complex stress modes to which these wires are subjected, their failure modes are also complex and most of them are unpredictable, requiring methods of verifying the integrity of pipes made up of probes and the like. These methods are very expensive to maintain, due to the need for constant analysis of the pipelines, keeping the research reason on the subject. The relationship between the mechanical strength of steels and the existing crystallographic texture is well known, evidencing the influence of the preferred crystallographic orientations in the structure with the resistance to crack formation and propagation. In this work, we investigate the evolution in texture, microstructure, and mechanical properties in wires with similar geometry to those found in flexible pipe armor in the application as tensile armor. The effect of different heat treatments on these materials on the mechanical properties and on the crystallographic texture is also analyzed. The pearlitic steel with 0.74wt%C was submitted to a bending procedure to assimilate the deformation procedure used industrially, which guarantees the integrity of the wire in the coil with guaranteed defect tolerance, evaluating the change in different stages of the process. processing. Annealing and patenting heat treatments were also carried out on this material, to obtain changes in microstructure and texture. The microstructural and texture evolution was characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and backscattered electron diffraction (EBSD). Then, to evaluate the mechanical properties, the samples were submitted to the Vickers microhardness test (HV). This work revealed that the flexural deformation procedure causes structural changes that provide an increase in the mechanical strength of the material. Bending strains intensify desirable texture components at the expense of undesirable components. These deformations to which the materials were subjected provide less mobility of dislocations, which causes an increase in mechanical strength. Little change in texture and microstructure is also observed. The heat treatments of annealing and patenting mainly modify the microstructure of the material, and in the case of patenting, the microstructure, according to the Hall-Petch relationship, increases the mechanical strength of the material, observed in the analysis of the microhardness of the material, while the Annealing provides the opposite effect. Annealing gives the material grains with ease of deformation, while patenting provides grain growth with high internal energy, with more resistance to deformation. Annealing increases the intensity of all texture components while patenting reduces the intensity.